Integrating Sustainable Maintenance into Sustainable Manufacturing Practices and its Relationship with Sustainability Performance: A Conceptual Framework - Ibrahim, Yousif Munadhil; Hami, Norsiah; Othman, Siti Norezam (International Journal of Energy Economics and Policy, 2019)
It appears that companies’ interest in achieving economic returns has made them neglect the environmental and social effects of their activities. With this imbalance in sustainability performance that causes environmental pollution and social damage, there is an urgent need to strike a balance between economic, environmental and social sustainability. Therefore, this study aims to achieve this balance in sustainability performance (SP) by providing a proposed framework that integrates sustainable maintenance (SMA) into sustainable manufacturing practices (SMPs). Effective adoption of SMPs and SMA has a significant positive influence on SP. Nevertheless, there are limited studies conducted on integrating SMA into SMPs and how it could impact SP. The theoretical contribution of the present study depends mainly on expanding existing knowledge about highlighting the moderating role of SMA on the relationship between SMPs and SP, including in the oil and gas industry (O&GI). Keywords: Sustainability Performance, Sustainable Manufacturing Practices, Sustainable Maintenance, Oil and Gas Industry JEL Classifications: Q52, Q56, Q58, Q38 DOI: https://doi.org/10.32479/ijeep.7709